Pengaruh Voucher Gratis Ongkir Terhadap Keputusan Pembelian Mahasiswa UIN SMH Banten Di Platform Shopee - Abdul Wahid Kohar; Ani Pebriani; Jumaedi Jumaedi; Wahyu Hidayat; Zaini Ibrahim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Students’ decisions to buy on the Shopee platform are influenced by various variables. Free shipping vouchers are one of them. The impact of providing free shipping coupons on purchases of the Shopee platform by students. Thirty-eight Shopee users who had received free shipping vouchers were given a questionnaire as part of the research technique. To evaluate the relationship between the independent variable (free shipping coupon) and the dependent variable (purchase choice), data analysis was carried out using basic linear regression. The results of the research show that there is a significant positive influence between providing free shipping vouchers on students’ purchasing decisions. This shows that providing free shipping vouchers can increase students’ interest and motivation to make purchases on the Shopee platform. The managerial implication of this research is that it is important for e-commerce platforms to consider the strategy of providing free shipping vouchers as a way to increase sales and influence consumer purchasing decisions. In addition, this research adds theoretical insight to knowledge about the variables that influence online shopping behavior, especially among students. The results of this research are intended to serve as a guide for future academics who wish to conduct studies on consumer behavior and marketing tactics in the digital era.